Zinc and vitamin A deficiency in a cohort of children with autism spectrum disorder. (16th April 2019) - Sweetman, Deirdre U.; O'Donnell, Sinead M.; Lalor, Annette; Grant, Tim; Greaney, Hilary
Abstract: Background and Objectives: Studies suggest that trace element and vitamin deficiencies are common in children with autism spectrum disorder (ASD). Data describing the rates of vitamin and trace element deficiencies in the ASD population of the northwest of Ireland is lacking. We wished to determine the prevalence of zinc and vitamin A deficiency in the ASD population compared with controls within this geographical area. Methods: Parents of children aged 2–18 years with ASD were invited to participate in the study. The control group consisted of well children attending the paediatric department for routine blood sampling. Children on vitamin supplements were excluded from both ASD and control groups. Informed written consent was obtained prior to recruitment. Samples were analysed for zinc and vitamin A levels according to standardized laboratory procedures. Results: Seventy‐four of the 150 children with ASD who were invited and 72 controls underwent blood sampling. Mean zinc and vitamin A levels were normal in both groups. There were significantly more males in the ASD group (88% versus 56%, p value < 0.001). The mean ( SD ) zinc level was not different between the groups (ASD 11.7 [1.7] versus control 11.6 [2.1] μmol/L, p value = 0.86). The mean (standard deviation) vitamin A level was higher in the ASD group (ASD 350.6 [82.6] versus 319.2 [82.8] μg/L, p value = 0.03), but this was likely confounded by age. Conclusion: Children with ASD in the northwest of Ireland have mean zinc and vitamin A levels within the normal range. It is important that these findings are relayed to health professionals and to parents of children with ASD so that informed decisions on vitamin supplementation can be made.